"Behold, I Make All Things New": The Unforgettable Message of the WCC Assembly in Uppsala in 1968. Issue 2 (23rd September 2018) - Moltmann, Jürgen
Abstract: The theme of the 4th Assembly of the World Council of Churches in Uppsala in 1968 was "Behold, I make all things new." God's great promise in Revelation precisely reflected the fears and hopes of the turbulent 1960s. This promise is realized in the experience of faith, and in this certainty, Christianity goes out to meet the great future of God in the world. The connection between this promised future and the advent of the new creation experienced by Christians was captured in Uppsala by the concept of "anticipation." This article traces the impetus of the impulse of the Uppsala assembly through the World Student Conference in Finland in 1968 and the Conference on World Mission and Evangelism in Bangkok in 1973–73.